STUDI FENOMENOLOGIS MEMAHAMI PENGALAMAN CYBERBULLYING PADA REMAJA - Lusi Alisah; S. Rouli Manalu (Interaksi Online, 2018)
This research starts from the number of cyber bullying events that occur among adolescents that continue to increase. Cyber bullying involves many aspects and has a certain impact on victims who experience it ranging from physical health, psychological to academic. This study aims to describe the experience of cyber bullying in adolescents in a manner that is in accordance with the perspective of victims who experienced it. This study uses a phenomenological approach using qualitative descriptive analysis methods. Research with a phenomenological approach tries to understand the meaning of an event and influence each other with humans in certain situations. Therefore, this study seeks to present an overall picture to understand the meaning of the experience of cyber bullying in adolescents through the perspective of victims. This research sourced from five informants who were the victims of cyber bullying by conducting indepth interviews. The findings show that cyber bullying is symbolic violence that continues from the real world to the world of social media / technology. Victims who experience cyber bullying also experience direct bullying in the real world. According to the victim, bullying behavior carried out on social media was more severe than what was carried out directly. The perpetrators of cyber bullying also show different behaviors by showing greater courage and aggressiveness on social media than in the real world. Cyber bullying causes fear of social media for victims who experience it. This fear is manifested in prudence in social media. In addition, cyber bullying creates pressure on victims. The pressure was responded differently by the victims through problem management to save / defend themselves from cyber bullying. The problem management or the pattern of saving / defending themselves from cyber bullying pressure on the victim depends on the pattern of social interaction, value system, age and its relationship to the ability to manage emotions and the forms of abuse experienced. Cyber bullying also affects academic performance with three types of impacts, such as negative, positive and neutral. This depends on the form of cyber bullying experienced, the ability to manage emotions and the support of people around the victim.